Uveitis associated to the infection by Leishmania chagasi in dog from the Olinda city, Pernambuco, Brazil - Juan Pablo Duque Ortiz (Ciência Rural, 2004)
Among the parasitic diseases, Canine Visceral Leishmaniasis (CVL) is included in the systemic illnesses of chronic evolution that attack men and dogs, presenting varied clinical manifestations as cachexia, dermatologic lesions, peripheral lymphadenopathies, besides the ocular lesions. This work report the case of a dog clinically suspected of having CVL, presenting skin lesions, cachexia, gryphosis, and ocular signs of uveitis. The parasitological diagnosis was accomplished for Canine Leishmaniasis through the visualization of amastigote forms of Leishmania chagasi in smears of bone marrow fluid aspirate, of non-lesioned, and lesioned skin. Alterations in the ocular structures are characterized mainly by mononuclear-plasmocitic infiltrate.